Research progress on fermentation of kefir and its application in disease prevention and adjuvant therapy - RUAN Hui, ZHU Yingying, LIN Simin, QIAN Xueqin, WANG Jing (Zhongguo niangzao)
Kefir is a kind of probiotic fermented foods with a long history, which is fermented by kefir grains (KG). KG are divided into milk kefir grains (MKG) and water kefir grains (WKG) according to different substrates, which are mainly composed of lactic acid bacterium and yeast, and is the main source for screening probiotic strains. In this paper, the fermentation strains and methods of milk kefir (MK) and water kefir (WK) were introduced, and their effects on the prevention and adjuvant therapy of intestinal dysfunction, liver protection and metabolic syndrome were summarized, providing theoretical basis for the discovery of probiotic strains and the research and development of functional fermented foods.